Chaos in strength and conditioning terminology - Waller, M.; Bonder, I.; Shim, A. (International Journal of Strength and Conditioning, 2023)
The field of strength and conditioning (S&C) has been adulterated with numerous, overlapping terms leading to miscommunication between athletes, sport coaches, strength and conditioning coaches (SCC) and sport scientists. Specifically, the use of various hyphenated terms to describe strength, in combination with contention associated with the proper definition and use of power, warrants the necessity to come to agreement on consistent terminology usage. Considerations should be based on the level of applicability and understanding of those most effected (athlete, sport coach, SCC, sport scientist). Moreover, while the use of kinetic and kinematic variables in describing strength and power related qualities is not incorrect, the population receiving the information must be considered. Athletes and sport coaches may be more influenced by simple cues and descriptors used to create movement intent and overall "buy in" to the S&C plan. Furthermore, SCC may be more concerned with how an exercise or movement will relate to improved sport performance while sport scientists may be more interested with how a specific variable(s) can be measured and quantified. Should the use of ambiguous, overlapping, or complex terminology persist, each of the various populations listed may continue to talk past one another instead of striving to be in agreeance with one another. Additionally, SCC may struggle with exercise selection and muddled programming due to the "paralysis by analysis" phenomenon when attempting to disseminate which exercises and movements to prescribe. Ultimately, the athlete may be most affected due to limited physiological improvement in turn leading to sub-par performance outcomes. Thus, the primary objectives of this article are to advance the field by creating an open discourse between the various individuals involved with the S&C profession while simultaneously shedding light on uncertainty associated with overlapping terms used to describe strength, power and other physical qualities associated with sports performance.